1990
DOI: 10.1111/j.1348-0421.1990.tb00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Proposals of Sphingomonas paucimobilis gen. nov. and comb. nov., Sphingomonas parapaucimobilis sp. nov., Sphingomonas yanoikuyae sp. nov., Sphingomonas adhaesiva sp. nov., Sphingomonas capsulata comb, nov., and Two Genospecies of the Genus Sphingomonas

Abstract: Based on the partial nucleotide sequence analysis of 16S ribosomal ribonucleic acid (rRNA), presence of unique sphingoglycolipids in cellular lipid, and the major type of ubiquinone (Q10), we propose Sphingomonas gen. nov. with the type species Sphingomonas paucimobilis (Holmes et al, 1977) comb. nov. From the homology values of deoxyribonucleic acid‐deoxyribonucleic acid hybridization and the phenotypic characteristics, three new species, Sphingomonas parapaucimobilis, Sphingomonas yanoikuyae, Sphingomonas ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
309
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 677 publications
(335 citation statements)
references
References 38 publications
24
309
0
2
Order By: Relevance
“…There was a good correlation between rRNA groups I to V and groups 1 to 5 based on cellular fatty acids and quinone systems. In the past two decades Pseudomonas species belonging to rRNA groups I1 to V or fatty acid and quinone groups 2 to 9 have been transferred to other genera (10,13,14,16,17,19,20). At this time, the genus Pseudomonas is restricted to Palleroni rRNA group I, and only the group I strains belong to the genus Pseudomonas sensu stricto.…”
Section: Resultsmentioning
confidence: 99%
“…There was a good correlation between rRNA groups I to V and groups 1 to 5 based on cellular fatty acids and quinone systems. In the past two decades Pseudomonas species belonging to rRNA groups I1 to V or fatty acid and quinone groups 2 to 9 have been transferred to other genera (10,13,14,16,17,19,20). At this time, the genus Pseudomonas is restricted to Palleroni rRNA group I, and only the group I strains belong to the genus Pseudomonas sensu stricto.…”
Section: Resultsmentioning
confidence: 99%
“…Many members of the Sphingomonas genera possess unique abilities in degrading refractory organic pollutants [26] and antagonizing phytopathogenic fungi [3]. Some members of the genus are involved in metal corrosion [1] and some are considered as potential opportunistic human pathogens [28].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Sphingomonas was proposed by Yabuuchi et al [28] to describe bacterial strains isolated from human clinical specimens and hospital environments. It was later found that this group of bacteria could also be isolated from natural sources, such as soil, rhizosphere, sediment, freshwater and marine environments [26].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Sphingomonas can be described as follows 26) . The cells are gram-negative, nonspore-forming, straight rods.…”
Section: Phylogenetic Characteristicsmentioning
confidence: 99%